Impact self-assembly of low-binder-content geopolymer parts - Kiwon Oh (Elsevier, 2021)
In the current study, we produce low-binder-content geopolymer parts through impact self-assembly. After sand (the filler) and a small amount of fly ash-alkaline activator mixture (the binder) are premixed, they are impacted by a hammer in a drop tower. The hammer mass is around 2∼5 kg and the drop distance is 0.2∼0.8 m. The flexural strength of the cured material is ∼5 MPa, comparable to typical portland cement. The key processing parameter is the impact momentum of the hammer. Repeated impact improves the microstructural uniformity. The low binder content helps minimize the materials cost, reduce the carbon emission, and lower the demand of class F fly ash.